一种体外模拟测定米饭升糖指数的方法 (2025)
本发明公开了一种体外模拟测定米饭升糖指数的方法，属于食品测量技术领域。本发明体外模拟方法包括模拟口腔咀嚼、胃肠消化、构建检测模型，能更准确预测米饭真实升糖指数GI。本发明方法解决了体内试验测定法需要以人为试验对象，技术难度大，成本高，时间长，可推广性与操作性差的问题；也弥补了Goni体外模拟测定方法忽视了口腔咀嚼过程对米饭消化的影响、无法准确反映米饭的真实消化情况、对不同类型米饭的区分度较差的缺陷；基于物性分析仪多重挤压装置模拟人类真实咀嚼过程，充分考虑咀嚼过程对米饭升糖指数的影响，进一步测定米饭在模拟胃肠消化环境中的消化速率，计算米饭升糖指数，结果更真实、客观、准确，对不同类型米饭区分度高。 The invention discloses a method for measuring the glycemic index of rice through in-vitro simulation, and belongs to the technical field of food measurement. The in-vitro simulation method comprises the steps of simulating oral chewing, gastrointestinal digestion and construction of a detection model, and the real glycemic index GI of rice can be predicted more accurately. The method disclosed by the invention solves the problems of high technical difficulty, high cost, long time and poor generalizability and operability due to the fact that a human test object is needed in an in-vivo test determination method; the defects that a Goni in-vitro simulation determination method neglects the influence of an oral chew